Didactical design of algebraic expression from a linear pattern with a realistic mathematics education approach - Fitriani, Nur; Sugiman, Sugiman; Arfah, Arfah (Jurnal Riset Pendidikan Matematika, 2023)
The design of didactic mathematics learning is designed by taking into account the learning barriers of students. This study aims to obtain a didactic design for learning algebraic expression from a linear pattern to reduce student learning barriers through the application of Realistic Mathematics  Education  (RME).  The  type  of  this  research  is  design research with three stages, namely the plan, do, and see. The research data  was in the  form of qualitative  data  with the  research instruments used were Hypothetical Learning Trajectory (HLT)on algebraic forms of  linear  patterns, student worksheet, pretest and  posttest, observation sheets,  teacher  interview  sheets,  and  student  interview  sheets  which were then analyzed retrospectively. This research constructs a didactic design in the form of a learning trajectory divided into nine stages and packaged  in  four  activities.  The  applied  didactic  design  opens  the thinking  process  for  students  to  find  the  meaning  of  variables  and algebraic   forms   of   the   mathematical   activities   themselves.   This didactical design is proven to reduce students' learning obstacles.